Parametric reform analysis of the Moroccan public pension system - Hind El-houjjaji; Abdellah Echaoui (Universitas Islam Indonesia, 2020)
In 2016, the government of Morocco adopted a parametric reformintended to deal with the critical financial situation of the CMR civilianpension regime. We examine the robustness of this reform using theCohort-Component population projection model to the fund'spopulation during the period 2014-2064. Then we lead a projection ofthe scheme financial situation. Moreover, we project the status quosituation and an alternative scenario where we propose to increase theretirement age solely, and then compare the results with those of the2016 parametric reform. Findings/Originality: For the threescenarios, a parametric reform will have a limited effect on the financialsituation, in both the long and the short-term. In long run, it is notsufficient to solve the problem of massive increase of pension schemedeficits while in short run it is not sufficient to eliminate the existingstructural problems neither to avoid the future financial deficit.Furthermore, our alternative scenario seems to have some moreadvantages, comparing with the other scenarios.